The Emerging Role of Neuropeptides in Parkinson’s Disease - Zheng, Yanan; Zhang, Linlin; Xie, Junxia; Shi, Limin (Frontiers in Aging Neuroscience, 2021)
Parkinson’s disease (PD), the second most common age-related neurodegenerative disease, results from the loss of dopamine neurons in the substantia nigra. This disease is characterized by cardinal non-motor and motor symptoms. Several studies have demonstrated that neuropeptides, such as ghrelin, neuropeptide Y, pituitary adenylate cyclase-activating polypeptide, substance P, and neurotensin, are related to the onset of PD. This review mainly describes the changes in these neuropeptides and their receptors in the substantia nigra-striatum system as well as the other PD-related brain regions. Based on several in vitro and in vivo studies, most neuropeptides play a significant neuroprotective role in PD by preventing caspase-3 activation, decreasing mitochondrial-related oxidative stress, increasing mitochondrial biogenesis, inhibiting microglial activation, and anti-autophagic activity. Thus, neuropeptides may provide a new strategy for PD therapy.